2017
DOI: 10.1039/c7cc04092j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological properties of triazole-linked locked nucleic acid

Abstract: We have synthesized and studied the biological and biophysical properties of triazole-linked ribo and xylo locked nucleic acid (LNA). The combination of LNA with the Isobe triazole linkage gave high binding affinity when incorporated at the 3' or 5' termini of oligonucleotides, but low binding affinity at internal positions. Antisense oligonucleotides (ASOs) and siRNAs containing triazole dimers were highly active and nuclease resistant. Surprisingly, the xyloLNA-modified siRNA was the most active of the serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Although, ASOs involving 2′‐ O ,4′‐ C ‐methyleneribofuranosyl‐nucleosides are known for high affinity recognition, their use is also accompanied with the risk of hepatotoxicity . This has persuaded researchers to explore modifications in their scaffold in pursuit of mitigation of the toxic effect while maintaining the antisense activity ,. Among other modifications, methyl substitution at their methylene bridge, i. e .…”
Section: Introductionmentioning
confidence: 99%
“…Although, ASOs involving 2′‐ O ,4′‐ C ‐methyleneribofuranosyl‐nucleosides are known for high affinity recognition, their use is also accompanied with the risk of hepatotoxicity . This has persuaded researchers to explore modifications in their scaffold in pursuit of mitigation of the toxic effect while maintaining the antisense activity ,. Among other modifications, methyl substitution at their methylene bridge, i. e .…”
Section: Introductionmentioning
confidence: 99%
“…In a related paper in this issue by Watts et al 28 the triazole-linked ribo and xylo-LNA gave high target RNA binding affinity when incorporated at the 3′ or 5′ termini of siRNAs, but extremely low binding affinity at internal positions. The triazole moiety was attached to the LNA sugars by more rigid linkers than the one studied here, and these results are not inconsistent with the above hypothesis.…”
mentioning
confidence: 95%
“… 21 23 There is also one report of this short triazole being combined with LNA and added to oligonucleotides by phophoramidite chemistry, but unlike our triazole, this particular linkage was strongly duplex-destabilizing despite the presence of LNA. 15 Another study described the synthesis of triazole-linked DNA by phosphoramidite chemistry using an inverted version of the triazole unit employed in this study, and this linkage slightly destabilized double-stranded DNA. 17 In contrast, in this study, we have shown that oligonucleotides (t-LNAs) that contain the triazole linkage in Figure 1 flanked by LNA on the 3′- or both sides (monomers X and Z , respectively) bind to their RNA targets with higher affinity and specificity than the equivalent unmodified ONs.…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, Watts et al found in contrast that LNA does not stabilize duplexes containing a more rigid four-atom triazole linkage internally. 15 Thus, the biocompatible six-atom triazole linkage and LNA (monomers X and Z , Figure 1 ) is a promising combination and warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%